Papuacocelus papuanus n. gen., n. sp. - a new Eurycanthinae from Papua New Guinea, with notes on the genus Dryococelus Gurney, 1947 and description of the egg (Phasmatodea: Phasmatidae: Eurycanthinae) - Hennemann, Frank H.; Conle, Oskar V. (Zootaxa, 2006)
The new genus Papuacocelus n. gen. (Type-species: Papuacocelus papuanus n. sp.) is described from Papua New Guinea (Morobe Province) and is related to Dryococelus Gurney, 1947, Thaumatobactron Günther, 1929 and Eurycantha Boisduval, 1835. The type-species Papuacocelus papuanus n. sp. is described and illustrated from both sexes. The male holotype is deposited in BMNH, the female paratype in the first author’s collection (FH). The monotypic genus Dryococelus Gurney, 1947 (Type-species: Karabidion australe Montrouzier, 1855) is briefly discussed and the eggs are described and illustrated for the first time. Keys and a table are presented to distinguish Dryococelus Gurney, 1947, Papuacocelus n. gen., Thaumatobactron Günther, 1929 and Eurycantha Boisduval, 1835. The beak-like ovipositor possessed by most females of Eurycanthinae is found to be formed by elongation of the anal segment and subgenital plate, and not as stated by former authors, by the subgenital plate and an elongated supraanal plate. A brief survey is provided of the beak-like ovipositors in Phasmatodea.